Penerapan Hukuman Mati Bagi Pelaku Tindak Pidana Korupsi - Muwahid Muwahid (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2015)
Research on the application of the death penalty for perpetrators of corruption is a research library , with the purpose to find out: first, setting the death penalty in law of corruption; secondly, the application of the death penalty for perpetrators of corruption in a human rights perspective. Primary data were obtained from the legislation, secondary data obtained from the criminal law books, law journals, and legal dictionaries. Data was collected to study the document. While the use of data analysis techniques "content analysis". The results showed; first, setting the death penalty in the Act eradication of corruption, there is only one article setting that article 2, paragraph (2) In the article explained that the death penalty can be applied to the perpetrators of corruption in " certain circumstances"; secondly, the application of the death penalty for corruptors if only textually examined, then the application of the death penalty is contrary to human rights as dicantukan in Article 28A paragraph (1), 28I (1), in conjunction with Article 4 of Law No. 39 of 1999, in conjunction with Article 3 of the Universal Declaration . However, if examined contextually by using extentif and teleological interpretation, the actual application of the death penalty does not conflict with Human Rights.